Quantum Gravity, Energy Wave Spheres, and the Proton Radius - Bender, Darrell (European Journal of Applied Sciences, 2024)
We argue, from present considerations and a previous analysis of the hydrogen atom as a miniature Michelson-Morley experiment in the Material Point Universe Revisited, that the electron wave velocity in the hydrogen atom is and that the fine-structure constant is the ratio of the remaining mass of the electron to the initial electron mass, not the ratio of velocities, as Sommerfield had it.